Integrating APOS Theory and Scaffolding in Islamic Boarding Schools: The Conceptual Design and Validation of APOSCAF Learning Model - Lisnasari Andi Mattoliang; Baso Intang Sappaile; Asdar Asdar (Cita konsultindo, 2026)
Mathematics education in Islamic boarding schools often faces unique pedagogical challenges, particularly in bridging traditional learning habits with the abstract cognitive demands of mathematical concepts. This study aims to develop and validate APOSCAF learning model, a conceptual integration of APOS (Action, Process, Object, Schema) theory and Scaffolding techniques, specifically designed for the Islamic boarding schools context. Using a Research and Development, the model was constructed through process of preliminary analysis and expert validation. The resulting APOSCAF learning model consists of five syntaxes. Expert judgment confirmed that the model is valid, indicating strong theoretical consistency and practical feasibility. This research contributes a culturally responsive yet cognitively rigorous framework, offering a strategic alternative for mathematics educators to enhance students' conceptual understanding within a religious-academic environment.